2004
DOI: 10.1038/sj.mp.4001563
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype of schizophrenia: a review and formulation

Abstract: The discovery of the pathophysiology(ies) for schizophrenia is necessary to direct rational treatment directions for this brain disorder. Firm knowledge about this illness is limited to areas of phenomenology, clinical electrophysiology, and genetic risk; some aspects of dopamine pharmacology, cognitive symptoms, and risk genes are known. Basic questions remain about diagnostic heterogeneity, tissue neurochemistry, and in vivo brain function. It is an illness ripe for molecular characterization using a rationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
154
0
7

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(164 citation statements)
references
References 154 publications
3
154
0
7
Order By: Relevance
“…63,64 Abnormal social interaction, that is, decreased non-aggressive social activity, may be correlated with negative symptoms of the disease. 1,2 Our results indicate that mutant expression of mutant hDISC1 led to impaired spatial spatial memory (the probe trial) without significantly affecting the performance of the mice during the training session. Notably, it was shown that the probe trial reflects spatial learning better than measure of escape latencies during training.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…63,64 Abnormal social interaction, that is, decreased non-aggressive social activity, may be correlated with negative symptoms of the disease. 1,2 Our results indicate that mutant expression of mutant hDISC1 led to impaired spatial spatial memory (the probe trial) without significantly affecting the performance of the mice during the training session. Notably, it was shown that the probe trial reflects spatial learning better than measure of escape latencies during training.…”
Section: Discussionmentioning
confidence: 69%
“…Live mice anesthetized by isoflurane were imaged with a 9.4 T nuclear magnetic resonance scanner (Bruker Biospin, Billerica, MA, USA). Fast-spin echo sequence was used for T 2 Image analysis. The images were processed using Amira (TGS, San Diego, CA, USA).…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
See 1 more Smart Citation
“…42,43 As the circuitry of corticocortical and thalamocortical projections in the PFC by and large relies on glutamate signaling, expression of glutamate receptors and their interacting PSD molecules in this area have been hypothesized to be altered in schizophrenia. In order to complement and expand on previous studies of abnormal expression of transcripts for glutamatergic proteins in schizophrenia, the present work contains an analysis of protein expression of NMDA receptor subunits and their interacting PSD molecules, PSD-95, SAP102, PSD-93 and NF-L in dorsolateral PFC (DLPFC) and anterior cingulate cortex (ACC).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the introduction of atypical antipsychotics, whose mechanism of action has been attributed to the antagonism of 5-HT2A receptors coupled to weaker antagonism of dopamine D2 receptors, only 10-20% of schizophrenic patients show a good outcome, recovering to pre-illness levels of functioning, while another 15-20% show a poor outcome and are considered treatment-resistant; the middle group exhibits a range of residual cognitive, psychotic, affective and psychosocial symptoms despite medications (Tamminga and Holcomb, 2005).…”
Section: Introductionmentioning
confidence: 99%